2022
DOI: 10.1186/s12890-022-01903-5
|View full text |Cite
|
Sign up to set email alerts
|

Lung clearance index to characterize clinical phenotypes of children and adolescents with cystic fibrosis

Abstract: Background Lung clearance index (LCI) is accepted as an early marker of lung disease in cystic fibrosis (CF), however the utility of LCI to identify subgroups of CF disease in the paediatric age group has never been explored. The aim of the study was to characterize phenotypes of children with CF using LCI as a marker of ventilation inhomogeneity and to investigate whether these phenotypes distinguished patients based on time to pulmonary exacerbation (PE). Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Our results confirm the clinical utility of MBWN 2 as a fundamental means to monitor lung disease in children with CF, tracking pulmonary abnormalities when spirometry is within the normal range ( 6 , 27 29 ). Combining results from MBWN 2 and exercise testing, we have further shown that LCI (both at 1/40th and 1/20th of the starting concentration) and ppWpeak are correlated, even in children with CF, and that these two measures can help profiling adolescents with normal FEV 1 .…”
Section: Discussionsupporting
confidence: 79%
“…Our results confirm the clinical utility of MBWN 2 as a fundamental means to monitor lung disease in children with CF, tracking pulmonary abnormalities when spirometry is within the normal range ( 6 , 27 29 ). Combining results from MBWN 2 and exercise testing, we have further shown that LCI (both at 1/40th and 1/20th of the starting concentration) and ppWpeak are correlated, even in children with CF, and that these two measures can help profiling adolescents with normal FEV 1 .…”
Section: Discussionsupporting
confidence: 79%
“…ETI, as well as ivacaftor alone for ivacaftor responsive mutations, are now referred to as highly effective CFTR modulator therapy (HEMT) [7], leaving previous modulators, lumacaftor-ivacaftor and tezacaftor-ivacaftor to be used only in age categories yet to receive ETI approval. We have seen a decrease in pulmonary exacerbation from 31 ]. Although the initiation of ETI therapy and the COVID-19 pandemic coincided, it is difficult to determine the true effects of ETI versus social distancing and the alteration in respiratory virus seasonality that followed the early pandemic.…”
Section: The Advent Of Highly Effective Modulator Therapymentioning
confidence: 85%
“…Chest radiographs have poor sensitivity with detecting early lung disease and even spirometry may not identify early disease. Therefore, new strategies to study and monitor lung function in infants and young children are being evaluated, such as magnetic resonance imaging (MRI) and lung clearance index (LCI) [29][30][31]. We hope these new modalities can help assess HEMT's efficacy in early lung disease and guide therapies in children.…”
Section: Emerging Priorities and Questions In The Era Of Highly Effec...mentioning
confidence: 99%
“…The lung clearance index (LCI), convective gas mixing in the conducting airways (Scond*VT) and the diffusion–convection interaction within the acinus (Sacin*VT), was measured using an open-circuit multiple breath washout (MBW) hard- and software package with nitrogen as tracer gas (N 2 MBW) (Exhalyzer ® D and Spiroware 3.3.1 Ecomedics AG, Switzerland), as described elsewhere. 19 The LCI in the children was considered normal when below 7.1. 20 …”
Section: Methodsmentioning
confidence: 99%